Penerapan Pijat Refleksi Kaki dalam Asuhan Keperawatan Pasien dengan Stroke - Dahlia Puspita; Hertuida clara (AKPER Pasar Rebo, 2023)
Stroke is the third leading cause of death in the world and the main cause of physical disability in productive and old age. Stroke is a term used to describe neurological changes caused by an interruption of the blood supply to a part of the brain. Complications that will occur in stroke sufferers is that it can cause death. The aim of the study was to gain real experience in providing nursing care and in applying foot reflexology therapy in patients with non-hemorrhagic strokes. The research method used is descriptive method with a case study approach accompanied by the application of evidence-based practices. The results obtained from this study are that nursing care can be applied to male patients, aged 51 years with non-hemorrhagic strokes, where there are five nursing problems, namely ineffective cerebral tissue perfusion, risk of decreased cardiac output, risk of nutritional deficits, physical mobility barriers, self-care deficits. At the implementation stage, the authors did 10-15 minutes of foot reflexology therapy with a frequency of 1x/day for 3 consecutive days to lower blood pressure. The evaluation results showed a decrease in blood pressure on the 1st day and an increase in blood pressure on the 2nd and 3rd day. The conclusion obtained is that there is a gap between research findings on foot reflexology and the application of foot reflexology that the author does on patients, because to see significant results it takes time and considering there are other factors that can affect the condition of clients who not only experience hypertension but also stroke. Hopefully the results of this study can provide information about the application of foot reflexology therapy to patients and their families to reduce blood pressure